Cornelis Verdonck (1563/64-1625): His Biography Revisited - Vanballenberghe, Nathalie (Journal of the Alamire Foundation, 2012)
Abstract For many years, the biography of the late-sixteenth- and early-seventeenth-century Flemish composer Cornelis Verdonck has been built on a combination of documents from the Spanish court in Madrid and documents found in Antwerp. Some biographers suggested the existence of two Cornelis Verdoncks living around the same period, but their claims have never been further investigated. New archival work has produced documents that prove that there were indeed several Verdoncks in Antwerp at the end of the sixteenth century, and that some important details regarding Verdonck’s life have been misinterpreted and misunderstood. This article thoroughly re-examines the available information, both new and existing, about Verdonck’s life, and disentangles the different pieces of information. A new biography of two separate Verdoncks-both musicians-emerges, confirming one Verdonck living and working in Antwerp, and another working at the Madrid court.